IDENTIFICATION OF YELLOW RUST (PUCCINIA STRIIFORMIS F.) TOLERANT SPRING WHEAT GENOTYPES AND FAVOURABLE ENVIRONMENT SUPPORTING DISEASE INCIDENCE - QAMAR, M; RASHID, K; KHAN, TN; ABBAS, SH; WAQAR, S; SHAKOOR, A; HUSSAIN, I; ASIM, M; ARSHAD, M; SOHAIL, M; KHURRAM, MM; USMAN, M; et al. (Biological and Clinical Sciences Research Journal, 2024)
In Pakistan, the wheat crop faces a significant threat from yellow rust disease caused by Puccinia Striiform F. The impact of this disease on yield varies with the growth stage and the plant's vulnerability. Wheat's diverse growing conditions, favorable weather patterns, and genetic makeup make it a substantial financial and nutritional value crop. The most cost-effective method for managing this issue is cultivating resistant strains. However, resistance in any variety can be overcome by mutation, necessitating ongoing development of new varieties. Research at the National Agricultural Research Centre Islamabad involved screening 50 wheat genotypes, including commercial varieties, new lines, and landraces, over two years (2021-2022 and 2022-2023). Three genotypes, NR-583, NR-559, and NR-559, demonstrated tolerance and high yields. These genotypes showed resistance over the past two years, unlike Pakistan-81 and Galaxy 13, which remained consistently vulnerable. Additionally, an analysis of environmental conditions over the same period revealed that disease proliferation is exacerbated by temperatures ranging from 10 to 20℃, humidity levels over 80%, and heavy rainfall.